De volta ao ponto de partida: o tempo cíclico em narrativas complexas nos filmes de ficção - Mauro Nascimento Clemente (2024)
This research seeks to understand the relation between the concepts of "time" in the construction of the complex narratives of the films Groundhog day (1993), by Harold Ramis; Run, Lola, run" (Lolla rennt, 1998), by Tom Tykwer; and Timecrimes (Los cronocrímenes, 2007), by Nacho Vigalondo; and how they used an alternative synthetic time model, the time loop. To this end, it will carry out a film analysis of these films, using the “Theory of narration”, by David Bordwell, in his work Narration in the fiction film (1985), as a methodological tool. It seeks to reflect on the relation of time and its possibilities with the practices of an audiovisual production, based on the theoretical contribution of authors such as Jacques Aumont, Marcel Martin, Belá Balázs, Andrei Tarkovski, Sergei Eisenstein, Gilles Deleuze, Allan Cameron, Robert Stam, among others. It is observed that these three films, in addition to qualifying themselves as complex narratives, also used a cyclical time model in the editing, which determines the circular narration when returning to the same emblematic moment of the story. This moment will be a kind of crossroads, in which the main characters will try to solve the problems posed by the plots. Back to this point of return, the protagonists can, then, experiment with different solutions, and, with each different action, a new possible ending will be generated.